Development and evaluation of multi nozzle backpack type power sprayer - SINGH, AVESH KUMAR; MANES, GURSAHIB SINGH; DIXIT, ANOOP; SINGH, S K; Singh, MANJEET (The Indian Journal of Agricultural Sciences, 2019)
The study deals the development and evaluation of a multi-nozzle backpack type power sprayer, which can be used to spray at all stages of cotton crop by using the boom both in horizontal (during early stages of crop) and in vertical (during maturity stage) position. Three types of nozzles N1, N2 and N3 were evaluated in the laboratory at three pressures P1 (3.0 kg/cm2), P2 (4.5 kg/cm2) and P3 (6.0 kg/cm2) and at three target distances D1 (540 mm), D2 (340 mm) and D3 (250 mm). Based on laboratory results, rate of discharge, angle of spray and swath width were found non-significant for nozzle N1 and N3. Therefore, nozzle N1 and nozzle N2 were selected for spraying on cotton crops at different stages of growth (60, 75, 90 and 105 days after sowing).Water sensitive paper was fixed on the plant at three locations of canopy (up and down of leaf). Uniformity coefficient and droplet density varied from 1.19 to 2.91 and 34.33 to 76.67. However, at a particular stage of crop the uniformity index and droplet density for some combination of locations was found non-significant. Field capacity of Nozzle N1 and N2 decreased from 0.34 ha/h to 0.09 ha/h and 0.28 ha/h to 0.09 ha/h when the position of boom was changed from the horizontal to vertical positions. Fuel consumption for spraying with nozzle N1 and nozzle N2 increased from 0.42 l/h to 0.60 l/h and 0.37 l/h to 0.50 l/h when the position of boom was changed from horizontal to vertical positions.